Partial Nephrectomy for a Massive Sporadic Renal Angiomyolipoma: Case Report and Review of the Literature - Jacob Albersheim-Carter; Molly Klein; Paari Murugan; Christopher J. Weight (Case Reports in Urology)
Introduction. Angiomyolipomas are the most common benign tumor of the kidney, associated with Tuberous Sclerosis in 20% of cases and arising sporadically in 80% of cases. Renal angiomyolipomas are neoplasms of mesenchymal origin with varying proportions of vasculature, smooth muscle spindle cells, and adipocytes, making management of such neoplasms a challenging endeavor. Possible management options include partial or radical nephrectomy and segmental renal artery embolization. Case Presentation. A 61-year-old woman admitted for a large retroperitoneal hemorrhage was discovered to have a giant, sporadic, 3818.3 g, 30.0 × 26.5 × 18.0 cm left perinephric angiomyolipoma. Given her hemodynamic instability upon presentation, she underwent segmental arterial embolization, followed by an open left partial nephrectomy. Ten-month follow-up revealed no noticeable loss of renal function. Discussion. Literature review revealed occasional renal angiomyolipomas of comparable size, with all angiomyolipomas larger than this requiring treatment with radical nephrectomy. Conclusion. We show that nephron-sparing surgery may be considered in the treatment of even the largest of renal angiomyolipomas.